(untitled) (Vietnam Journal of Community Medicine, 2024)
Aims: This study aims to assess the prevalence of acne and identify factors associated with its occurrence among students at Đại Nam University. Methods: A cross-sectional study was conducted involving 508 students. Participants were surveyed on demographics, lifestyle habits, and family history of acne. Data were analyzed to determine the association between these factors and the prevalence of acne. Results: The prevalence of acne among the participants was 49.8%, with a slightly higher prevalence in females (50.8%) compared to males (48.0%). Family history of acne was significantly associated with the likelihood of developing acne, with students having family members with acne being 48% more likely to have acne (AOR: 0.48; 95% CI: 0.33-0.71; p<0.001). Students who spent between 500,000 and 1,000,000 VND per month on skincare products had a 53% lower rate of acne compared to those who did not spend money on cosmetics (COR: 0.53; 95% CI: 0.31-0.90, p<0.05). No significant associations were found between other personal characteristics or lifestyle habits and acne prevalence. Conclusions: Acne is common among students at Dai Nam University, with family history and skincare spending being significant factors in its prevalence. Health education programs on skincare may help prevent acne and improve awareness among students. Further research is needed to explore the biological and environmental factors influencing acne in young adults.